Pengembangan Perangkat Pembelajaran Menulis Narasi Berbasis Media Bagan Pohon di Kelas V Sekolah Dasar - nur jani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The difficulty of students in writing narratives is a problem that has been found in the field. Students lack mastery in giving an idea and developing it into a narrative essay. The purpose of this research is to create a learning tool for writing narratives based on tree chart media that is valid, practical, and effective. The type of research used is development research with the ADDIE model. The teacher and the fifth grade students of SD Islam Al-Azhar Simabur are the subjects of this study. Looking at the research data with the validity test, which was obtained from the validation sheet of the learning device. Then to see the practicality data from the observation sheet on the implementation of the lesson plans, along with the teacher and student response questionnaires. Activities and assessments of student learning outcomes are obtained from the effectiveness of learning tools. The results of the validation of learning tools that have been carried out are stated in the very valid category. The learning tools developed are also stated to be very practical, this is supported by the RPP implementation sheet with an average of 90 and the teacher's response 89 then students 91. After that, it can be seen that the results of student activities and student learning outcomes are very satisfying so that it can be stated very effective when applied in learning. In summary, the learning tools developed using the tree chart media in fifth grade elementary school were declared valid, practical and effective.